Identifikasi Tipe Diskalkulia Pada Siswa MTs Ar Riyadh Materi Aritmatika - Suraj, Ach. Siddik; Lutfiyah, Lutfiyah; Murtinasari, Frida (Universitas Islam Jember, 2025)
The research conducted at Mts Ar Riyadh is a research with qualitative descriptive method research conducted with the aim of knowing the difficulties experienced by some identified students who are still unable to explain and distinguish a form and are not fluent in operating simple arithmetic material. The subjects of this study consisted of 2 students in class IX. Data collection tools were observation, test, and interview. Data analysis was carried out using qualitative descriptive analysis techniques. The results of this study found that S1 was identified with dyscalculia in the types of dyscalculia, namely, weak in logic, weak in planning, diligent in tasks, and inability to calculate simply. Meanwhile, subject S2 was identified with dyscalculia in terms of inability to calculate simply. Keywords: arithmetic and dyscalculia